Deep structure and Pb-Zn mineralization control of the Shuangdinggou-Xinling rock body in the Qingchengzi ore field revealed by gravity profile inversion - Liu, Yingchun; Yu, Yunliang; Gao, Xiangwei; Cai, Hongchen; He, Jinxin (Frontiers in Earth Science, 2025)
The Qingchengzi region in Liaoning Province represents a significant Pb-Zn ore site in China. The Late Triassic Shuangdinggou-Xinling granite intrusions, located in both the southern and northern parts of this mineral-rich area, critically influence the genesis of Pb-Zn deposits. The limited investigation into the deep distribution characteristics of these granite bodies hinders our understanding of their potential for deep-seated mineral deposits. We conducted an integrated approach that encompassed geological surveys, geochemical analyses, and Bouguer gravity anomaly assessments. The geochemical investigations of the Shuangdinggou and Xinling granite bodies indicated analogous signatures, reinforcing their collective contribution to the generation of ore-forming fluids. Furthermore, the gravity data demonstrated that the Shuangdinggou and Xinling granite bodies are interconnected at depth, with the Shuangdinggou body exhibiting a burial depth ranging from approximately 4,000–4,500 m. By employing human-machine interactive gravity profile inversion across two cross-sections, we have clarified the extensive subsurface morphology of the granite formations and validated their hidden interconnections. In the Qingchengzi mining zone, the Xinling body (granite branch) extends northeastward from the Shuangdinggou body (granite base) along a fault. These granite intrusions jointly govern the formation and spatial distribution of Pb-Zn deposits, influenced by overlaps of syngenetic fractures resulting from magmatic intrusions and earlier tectonic folding events.